0852 Geriatric Health Conditions And The Combined Outcome Of Poor Sleep Quality With Objective Short Sleep Duration. (27th May 2020) - Miner, B; Vaz Fragoso, C A; Han, L; Yaggi, H K; Redeker, N S; Stone, K L
Abstract: Introduction: Poor sleep quality with objective short sleep duration (≤6 hours) is a high-risk phenotype. The associations of geriatric health conditions with this sleep phenotype have not been described. Methods: Using data on 3, 127 older women from the Study of Osteoporotic Fractures (SOF), mean age 84 years, and 3, 058 older men from the Osteoporotic Fractures in Men Sleep Study (MrOS), mean age 76 years, we evaluated cross-sectional associations between geriatric health conditions and the combined outcome of poor sleep quality with actigraphic short sleep duration. Geriatric health conditions included cognitive impairment (modified MMSE score 1.5SD below the cohort mean value), physical impairment (inability to do a chair stand), falls (≥2 in past year), and vision impairment (acuity ≤20/40). Poor sleep quality was defined by Pittsburgh Sleep Quality Index (PSQI) score >5 and short sleep duration by average total sleep time ≤6 hours from wrist actigraphy (averaged over ~5 days). Women (SOF) and men (MrOS) were evaluated separately and multivariate logistic regression models also included age, race, education, comorbidities (medical, psychiatric, and primary sleep disorders), and medication use. Results: Poor sleep quality with actigraphic short sleep duration was present in 475 (15.6%) men and 400 (13.1%) women. In men, the unadjusted odds of having combined poor sleep quality with actigraphic short sleep duration were statistically higher with cognitive impairment (OR=1.45 [CI 1.05, 1.98]), physical impairment (2.90 [1.87, 4.51]), and falls (1.97 [1.48, 2.62]). In women, the unadjusted odds of having combined poor sleep quality with actigraphic short sleep duration were statistically higher with physical impairment (1.54 [1.16, 2.04]) and falls (1.63 [1.21, 2.20]). However, these associations were no longer statistically significant in adjusted models (men and women). Conclusion: Older persons with geriatric health conditions are more likely to have the combined phenotype of poor sleep quality with actigraphic short sleep duration, but this association is likely explained by comorbidity and medication use. Support: Dr. Miner is supported by the Yale Claude D. Pepper Older Americans Independence Center (P30AG021342), the American Academy of Sleep Medicine Foundation, a foundation of the American Academy of Sleep Medicine, and the National Institute on Aging T32AG019134.